(untitled) (Research, Society and Development, 2026)
Objective: To analyze the relationship between oral health–related quality of life, prosthetic status, and the presence of oral mucosal alterations in institutionalized Peruvian older adults residing in a geriatric institution. Materials and Methods: An observational cross-sectional study was conducted in 51 older adults who were removable denture wearers and residents of a public institution in Lima, Peru. Oral mucosal alterations were assessed through intraoral clinical examination according to the criteria established by the World Health Organization, in addition to the evaluation of prosthetic status and denture hygiene. Oral health–related quality of life was assessed using the Geriatric Oral Health Assessment Index (GOHAI). Nonparametric tests and multiple linear regression models were used to explore associations. Results: A total of 68.6% of the participants presented oral mucosal alterations, with denture stomatitis and inflammatory fibrous hyperplasia being the most frequent conditions. The presence of these alterations was associated with the use of complete removable dentures, prosthetic misfit, prolonged use, and poor denture hygiene. Older adults with mucosal alterations showed lower scores in oral health–related quality of life, particularly in the psychosocial and pain dimensions. Conclusion: Oral mucosal alterations associated with the use of removable dentures significantly affect oral condition and quality of life among institutionalized Peruvian older adults, highlighting the need for periodic clinical follow-up and preventive strategies in this population group.